Analysis of high school students’ misconceptions in Bantul District on the material of the human movement system using the CRI method - Utami, Dheyanti Wahyu; Kurniawati, Atik (Universitas Negeri Yogyakarta, 2026)
This study aims to (1) analyze the level of misconceptions of class XI students that occur in the material of the Human Movement System in Bantul Regency using the Certainty of Response Index (CRI) method; (2) analyze which sub-materials students experience the most misconceptions in the material of the Human Movement System. This study is descriptive and uses a quantitative approach. The population in this study was class XI students of State Senior High Schools in Bantul Regency. The sample was determined using the cluster random sampling technique. The data collection technique used was the Certainty of Response Index (CRI) method, and the data collection instrument used was Selected Response Items in the form of multiple-choice tests. The results of the study showed that students’ misconceptions in the Human Movement System material averaged 41.7% overall, falling within the moderate category. The percentage of misconceptions in the sub-concepts (1) structure and function of bones, (2) structure, function, and mechanism of muscle contraction, (3) structure and function of joints, and (4) disorders and abnormalities in the human movement system, respectively, were 44.75%; 40.25%; 35.31%; and 46.48%. This research is crucial for identifying misconceptions among high school students, thereby improving the quality of learning.